Analisis Faktor Penyebab Ketidaktahuan Pengendara Sepeda Motor dalam Mengguankan Helm di Jalan Raya - Annisa, Nur; Pane, Sabrina Umami; Pandiangan, Inriyani; Sitepu, Nazwa Sabila; Manalu, Syuratti Astuti Rahayu (CV. PUSDIKRA MITRA JAYA, 2025)
Traffic safety is a crucial aspect in maintaining public security amid increasing mobility and vehicle density on the roads. One of the main forms of protection for motorcycle riders is the use of helmets, which have been proven effective in reducing the risk of head injuries and fatalities caused by accidents. However, many riders still fail to comply with this regulation due to factors such as habit, comfort, risk perception, weak law enforcement, and social influence. This study employs a descriptive qualitative method through observation and interviews with several riders to identify the causes of non-compliance in helmet use. The results show that although most riders understand the importance of wearing helmets, this awareness has not yet translated into consistent behavior. The main reasons for non-compliance include short travel distances, discomfort, and the lack of police enforcement. The impact of this disobedience increases the risk of fatal accidents, weakens social discipline, and imposes greater economic and social burdens on society. Therefore, comprehensive efforts are needed through strict law enforcement, continuous education, and the development of a culture of discipline from an early age so that road safety becomes a shared responsibility.